Regulation mechanism of ferroptosis and its research progress in tumor immunotherapy - Xu, Jing; Lin, Xiaolin; Han, Ting; Zhou, Qingqing; Su, Yang; Jiang, Shuqing; Xiao, Xiuying; Liu, Tengfei (Frontiers in Molecular Biosciences, 2022)
Ferroptosis is a novel regulatory cell death, which is characterized by iron dependency and mainly caused by accumulation of intracellular lipid peroxides and reactive oxygen species. Ferroptosis plays an important role in the occurrence and development of a variety of malignant tumors, especially in anti-tumor treatment. As an emerging treatment method, the immunotherapy has been widely applied in the clinical practice, and the role of ferroptosis in tumor immunotherapy has been gradually explored. This study aims to illustrate the features of ferroptosis, and its role in anti-tumor immunotherapy and potential clinical application.